The role of midwifery students in contraceptive counseling role play: evaluation of the tpack approach - Endang Khoirunnisa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to evaluate the effectiveness of the TPACK (Technological, Pedagogical, and Content Knowledge) approach in contraceptive counseling training through role play for fourth-semester DIII Midwifery students in the Family Planning (KB) Services course. This research uses a qualitative approach with a case study research design. Data was collected through in-depth interviews with 15 students as research participants. The research results show that students understand the TPACK concept well and see it as a practical approach to learning contraceptive counseling. Integrating technology, pedagogy, and content in learning is considered to help students understand the material better. Role play has proven effective in honing students' contraceptive counseling skills and increasing their confidence in facing real counseling situations. This research also identified several challenges, such as limited access to technology. Therefore, efforts are needed to increase technological support and sustainable development in implementing TPACK in health education. Overall, the TPACK approach has great potential in improving the quality of contraceptive counseling learning and preparing midwifery students to become competent counselors.